Tax Incentives to Hedge - Graham, John R.; Smith, Clifford W. (Journal of Finance, 1999)
For corporations facing tax‐function convexity, hedging lowers expected tax liabilities, thereby providing an incentive to hedge. We use simulation methods to investigate convexity induced by tax‐code provisions. On average, the tax function is convex (although in approximately 25 percent of cases it is concave). Carrybacks and carryforwards increase the range of income with incentives to hedge; other tax‐code provisions have minor impacts. Among firms facing convex tax functions, average tax savings from a five percent reduction in the volatility of taxable income are about 5.4 percent of expected tax liabilities; in extreme cases, these savings exceed 40 percent.